Predictive value of laboratory parameters in childhood migraine - Poyrazoglu, Hatice Gamze; Ozturk, Agah Bahadir (Springer Heidelberg, 2020)
Migraine is a neurovascular disease characterized by inflammation of the cerebral and extra cerebral vessels and appears in the form of attacks. Although the pathophysiology of migraine is not fully known, the data obtained because of long-term studies reliably support the presence of a potential relationship between migraine pathogenesis and platelet biology. The aim of this study was to investigate the effect of migraine on MPV and other blood parameters as well as the relationship between the hematologic parameters and characteristics of the headache and whether they possess diagnostic value as inflammation and platelet biology play a fundamental role in the disorder. The study group consisted of 56 patients who were followed up and treated with a diagnosis of migraine and 45 healthy patients. The median creatinine, CRP and TSH values of the children in the migraine group were found to be statistically significantly higher than the healthy control group. Serum iron levels of the migraine group were found to be statistically significantly lower than the control group. No statistically significant difference was found between the two groups in terms of MPV. However, when we examined only the patient group, we found MPV to be statistically significantly higher in girls. Increased MPV and decreased serum iron levels may be related to migraine. More comprehensive studies including a larger population are required to evaluate the specific parameters that may guide the follow-up and treatment of the disorder with simple tests to be used in routine practice and to elucidate the underlying pathophysiology.
Keywords: Migraine; Mean platelet volume; Childhood; Inflammation